Population Pharmacokinetic Analysis of Atomoxetine and its Metabolites in Children and Adolescents with Attention‐Deficit/Hyperactivity Disorder - Cheng, Shen; Al‐Kofahi, Mahmoud; Leeder, J. Steven; Brown, Jacob T. (Clinical pharmacology and therapeutics, 2024)
Atomoxetine (ATX) is a non‐stimulant used to treat attention‐deficit/hyperactivity disorder (ADHD) and systemic exposure is highly variable due to polymorphic cytochrome P450 2D6 (CYP2D6) activity. The objective of this study was to characterize the time course of ATX and metabolites (4‐hydroxyatomoxetine (4‐OH); N‐desmethylatomoxetine (NDA); and 2‐carboxymethylatomoxetine (2‐COOH)) exposure following oral ATX dosing in children with ADHD to support individualized dosing. A nonlinear mixed‐effect modeling approach was used to analyze ATX, 4‐OH, and NDA plasma and urine, and 2‐COOH urine profiles obtained over 24–72 hours from children with ADHD (n = 23) following a single oral ATX dose. Demographics and CYP2D6 activity score (AS) were evaluated as covariates. Simulations were performed to explore the ATX dosing in subjects with various CYP2D6 AS. A simultaneous pharmacokinetic modeling approach was used in which a model for ATX, 4‐OH, and NDA in plasma and urine, and 2‐COOH in urine was developed. Plasma ATX, 4‐OH, and NDA were modeled using two‐compartment models with first‐order elimination. CYP2D6 AS was a significant determinant of ATX apparent oral clearance (CL/F), fraction metabolized to 4‐OH, and systemic exposure of NDA. CL/F of ATX varied almost 7‐fold across the CYP2D6 AS groups: AS 2: 20.02 L/hour; AS 1: 19.00 L/hour; AS 0.5: 7.47 L/hour; and AS 0: 3.10 L/hour. The developed model closely captures observed ATX, 4‐OH, and NDA plasma and urine, and 2‐COOH urine profiles. Application of the model shows the potential for AS‐based dosing recommendations for improved individualized dosing.